IWHELD, A Novel Digital Non‐Pharmacological Intervention with Live Virtual Coaching Reduces Antipsychotic Use in Nursing Home Residents with Dementia Compared to Usual Care in a 16‐week RCT. (20th December 2022) - Ballard, Clive G; McDermid, Joanne; Aarsland, Dag; Khan, Zunera; Sweetnam, Adrienne
Abstract: Background: Implementation of evidence‐based training into real world practice in nursing home settings is a major challenge. Digital approaches provide real potential to addressing the barriers, particularly over the difficult period of the COVID‐19 pandemic. Method: iWHELD is a first‐of‐its‐kind digital programme evolving the principles of the WHELD intervention combining person centred care, social interaction, and antipsychotic review, combining virtual coaching with a digital resource for nursing homes. The intervention utilising a Dementia Champion model supported by live virtual coaching set within a digital resource hub and peer networking platform was compared to usual care in a 16‐week randomised control cluster study of 741 people with dementia across 149 nursing homes in the UK. The initial outcomes evaluated are the use of antipsychotic drugs and neuropsychiatric symptoms (using the Neuropsychiatric Inventory NH). Result: 36/72 (53%) of nursing homes allocated to the active treatment arm engaged successfully with the digital intervention, with 563 residents completing the treatment period. The average age of residents was 84.5 years, 71% were female, and there were no significant differences between treatment arms. There was a significant reduction in antipsychotic use in the digital iWHELD treatment group from 49% to 31% compared to no change in the group receiving usual care (p = 0.046). Initial analysis of neuropsychiatric symptoms indicates a non‐significant improvement in the intervention group compared to those receiving usual care. Conclusion: The current RCT using an online programme with live virtual coaching delivered through a Dementia Champion achieved better than 50% engagement, which compares favourably with previous studies of digital interventions in other therapeutic areas. The intervention also achieved significant reductions in antipsychotic use without any worsening of neuropsychiatric symptoms, and provides an important potential approach to safely reducing the rise in antipsychotic use in nursing home residents with dementia that has become a major challenge during the COVID‐19 pandemic.